A Symmetrical Cross-Connected T-Type Multilevel Inverter With Reduce Device Count - Rathore, Vishal; Kumar, Dhananjay; Mundra, Prateek (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2023)
This paper presents a symmetrical, cross-connected T-type (CT-type) multilevel inverter (MLI) configuration with reduced device count (RDC). It comprises eight power switches, two DC sources, and four capacitors with self-voltage balancing. The generalized topology is formed by two CT-type basic modules connected by two power switches. These topologies operate using DC sources and capacitors having the same or different voltage levels, which can be extended by cascading the modules to attain a higher voltage level suitable for high-power applications. Therefore, the proposed CT-Type MLI is a good choice for renewable energy applications that require a lower input voltage source magnitude to attain high voltage levels. This paper uses the Matlab/Simulink platform to simulate the proposed CT-type topology using the level-shifted pulse width modulation (LS-PWM) technique. Further, a laboratory prototype is developed to test and validate the feasibility and effectiveness of the proposed MLI. Finally, a comparative analysis of the number of DC sources, capacitors, power switches, drivers, and total standing voltage (TSV) is presented against similar recent topologies.